Peningkatan Keamanan Dan Kenyamanan Jamaah Masjid Al-Anwar Melalui Renovasi Halaman Masjid - Guntur Nugroho; Arini Hidayah; Suwarto Suwarto (Universitas 45 Surabaya, 2023)
Al Anwar Mosque is located in Sawahan Pendowoharjo Sewon Hamlet, Bantul. Currently, the mosque management is planning to renovate the mosque yard in the form of installing paving blocks as a pavement layer. The courtyard of the mosque is still dusty soil, so that in the rainy season it becomes muddy and disturbs the comfort of people who come to worship in the mosque. Funding and technical assistance are the main problems in the renovation program of the pavement layer of the mosque courtyard. On the basis of these problems, it is necessary to carry out community service in the form of funding and also technical assistance for the renovation of the pavement layer of the mosque courtyard. The results of community service activities increase the safety and comfort of Al Anwar mosque worshippers.